Successful hybrid surgery for ileal conduit stomal varices following oxaliplatin-based chemotherapy in a patient with advanced colorectal cancer - Hideo Uehara; Hirofumi Kawanaka; Tomonori Nakanoko; Masahiko Sugiyama; Mitsuhiko Ota; Yohei Mano; Keishi Sugimachi; Masaru Morita; Yasushi Toh (Surgical Case Reports)
Abstract Background Ectopic variceal bleeding is a rare but life-threatening complication of portal hypertension (PH). Oxaliplatin-based chemotherapy for colorectal cancer (CRC) is associated with sinusoidal obstruction syndrome of the liver, which can lead to PH. Case presentation Here, we report a successful hybrid surgery that included intraoperative obliteration of ileal conduit stomal varices (ICSVs) for a 66-year-old woman with CRC and liver metastasis that had been treated multimodally during the previous 4 years, including 17 courses of oxaliplatin-based chemotherapy. She was admitted to our hospital for massive hemorrhage from an ileal conduct stoma. Image findings showed ICSVs as a part of portosystemic shunt, which were afferently supplied from the superior mesenteric vein (SMV) and drained by the numerous cutaneous veins connected to the left femoral vein. Obliteration of the stomal varices by interventional radiologic techniques alone was inappropriate because of difficulties of cannulating the efferent cutaneous veins. We, therefore, performed hybrid surgery for the ICSV, which included cannulation into the SMV branch and antegrade obliteration of the varices with a 5% solution of ethanolamine oleate with iopamidol under blocking the SMV flow, using a vascular clip and ligation. Hemorrhage in her ileal conduit stoma disappeared completely. Conclusion Customized treatment of ectopic varices should be based on their precise vascular anatomy; hybrid surgery with intraoperative angiography is an alternative treatment for ectopic varices such as ICSV.